Determination of element contents of commercial and homemade jams - Kántor, Andrea; Alexa, Loránd; Kovács, Béla; Czipa, Nikolett (Acta Agraria Debreceniensis, 2018)
Various products could be prepared by using fruits as raw materials. In Hungary, the most popular fruit products are spirit, jams, preserves, juices and dried fruits. Jams are made from different fruits, with different fruit content, technology and additives. They can be used for different products or they can be consumed by themselves. These products and their related production processes have great traditions in Hungary. In addition, they are widely used. The aim of our study was to determine the element content of jams and to compare these samples based on their micro- and macroelement content. In this study, 26 fruit jams with different botanical origins were examined. 10 samples were commercial, and 16 samples were homemade products. The determination of micro- and macroelements was carried out by using Inductively Coupled Plasma Mass Spectrometer and Inductively Coupled Plasma Optical Emission Spectrometer. Different element contents were measured [B (249.7), Ca (422.6), Fe (259.9), K (769.8), Mg (280.2), Na (589.5), P (185.9), S (182.0), Al (27), Mn (55), Cu (65), Zn (66), Sr (88), Ba (137)]. Based on element contents, the jams showed statistical differences.